2021
DOI: 10.1039/d1cp03822b
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics and energetics of viral RNA recognition by lab-evolved proteins

Abstract: The conserved and structured elements in viral RNA genomes interact with proteins to regulate various events in the viral life cycle and have become key targets for developing novel therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…We reported the uncertainities in the averaged Δ G comp and Δ G free as the standard error of the mean (from three replicas) and calculated the error in the final ΔΔ G by computing the standard error of the mean associated with the averaged Δ G values. We obtained a good convergence and a reasonable statistical uncertainty (<1 kcal/mol) of the computed energetics (ΔΔ G ). , …”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…We reported the uncertainities in the averaged Δ G comp and Δ G free as the standard error of the mean (from three replicas) and calculated the error in the final ΔΔ G by computing the standard error of the mean associated with the averaged Δ G values. We obtained a good convergence and a reasonable statistical uncertainty (<1 kcal/mol) of the computed energetics (ΔΔ G ). , …”
Section: Methodsmentioning
confidence: 60%
“…Many RNA binding proteins recognize RNA molecules through arginine-rich motifs (ARMs), as they are relatively shorter in length, have little sequence similarity (aside from containing many arginine residues), and adopt diverse conformations (including an α-helix and a β-hairpin) upon association with the viral RNA. The experimental work using X-ray crystallography and nuclear magnetic resonance (NMR) methods on the peptide–RNA complexes has demonstrated that the RNA backbone interacts with peptides more commonly than the nucleotide bases, suggesting that the majority of peptide–RNA interactions are nonspecific. , Overall, these studies showed that the peptide–RNA interactions occur through dynamic rearrangements in both molecules, which often entail backbone shifts and the flipping of nucleobases and amino acid residues. , Moreover, recent studies have demonstrated that the β-hairpin peptides could be synthesized with ultrahigh affinity toward viral RNA molecules. However, a de novo design of α-helical peptides that potently and selectively recognize viral RNA molecules is limited due to a poor understanding of the RNA recognition mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found through earlier structural, classical simulation, and quantum chemical studies that ATP generally binds at the active site of aaRS in a bent conformation with its α-phosphate pointed toward the adenine base and its β- and γ-phosphate moieties oriented toward the opening of the active site. ,,,, For all class II aminoacyl tRNA synthetases, the adenine ring of ATP gets stacked with the conserved phenylalanine of motif 2 and arginine of motif 3 . Also, the invariant motif 2 arginine binds rather strongly with the α-phosphate of ATP, while one Mg 2+ ion bridges the α- and β-phosphates. ,, The presence of one or two additional Mg 2+ ions bridging the β- and γ-phosphates of ATP has also been reported in earlier experimental and theoretical studies. ,,,,, Recent simulations have shown that the conserved motif II arginine residue makes contact with both the α-phosphate and attacking oxygen of the carboxylic group of the substrate amino acid and thus helps in anchoring the substrates ATP and amino acid in the reactive conformation. ,, This residue has also been reported to stabilize the transition states of both the activation and transfer steps. ,, Experimental and quantum chemical studies on the effects of mutation of the motif 2 arginine have also shown its important role in catalytic reactions at the active site of class II aminoacyl tRNA synthetases. ,,, The important role of arginine residues has also been reported for biomolecular recognitions involving other proteins and RNA. , …”
Section: Introductionmentioning
confidence: 99%
“…13,25,28,29 The important role of arginine residues has also been reported for biomolecular recognitions involving other proteins and RNA. 30,31 Although several experimental and computational studies have been carried out on the adenylation step of aminoacylation process, 13−16,24,32−40 there still exists a lacunae of knowledge for some of the important details such as the free energy landscape of the fully solvated reacting system at finite temperature, reaction pathway, and free energy barrier including entropic contributions for passage of the solvated system from reactant to the product state in aqueous medium, and also how mutation of some of the key active site residues of the enzyme affects the free energy landscape and activation free energy of the reaction in aqueous medium. Moreover, the formation of the transition state and structural evolution of reactants to the product state through the transition state involving breaking and formation of chemical bonds during the course of a dynamical simulation, as opposed to static structure calculations, are important goals that are yet to be realized for an aminoacylation process including the adenylation step.…”
Section: Introductionmentioning
confidence: 99%